2019
DOI: 10.1093/schbul/sbz022.025
|View full text |Cite
|
Sign up to set email alerts
|

7.3 Polygenic Risk for Schizophrenia Moderates the Influence of Childhood Adversity on Daily-Life Emotional Dysregulation and Psychosis Proneness

Abstract: Background: Psychotic like experiences (PLEs) are frequently found among children from the general population. PLEs are often transitory phenomena, but are for some predictive of later psychopathology, e.g. psychotic disorders and non-psychotic disorders. For both schizophrenia and bipolar disorder, the single largest risk factor for developing the disorder is a positive family history of the disorder. Therefore, early antecedents of schizophrenia and bipolar disorder can be identified by studying children of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…14 However, summer birth was also previously associated with deficit schizophrenia and might therefore be evaluated as an exposure as well. 24,25 Considering evidence showing that common environmental factors (eg, childhood adversity) are not specific to the psychosis phenotype but instead are more generally related to psychopathology, 26,27 the ES would likely (to a degree) be associated with other mental disorders in mixed samples. Therefore, a low discriminant capacity for the ES should be anticipated.…”
Section: Limitations Of Exposome Scorementioning
confidence: 99%
“…14 However, summer birth was also previously associated with deficit schizophrenia and might therefore be evaluated as an exposure as well. 24,25 Considering evidence showing that common environmental factors (eg, childhood adversity) are not specific to the psychosis phenotype but instead are more generally related to psychopathology, 26,27 the ES would likely (to a degree) be associated with other mental disorders in mixed samples. Therefore, a low discriminant capacity for the ES should be anticipated.…”
Section: Limitations Of Exposome Scorementioning
confidence: 99%
“…The network analysis of the ESM data revealed that proxy genetic liability for psychopathology was associated with more densely connected network structure of the emotions, which include 'cheerful ', 'insecure', 'relaxed', 'anxious', 'irritated' and 'down' items (Hasmi et al, 2017). A recent gene-environment interaction study using the ESM data has demonstrated that polygenic risk score for schizophrenia interacts with childhood adversities to influence negative effect, positive effect and subtle psychosis expression (Pries, Klingenberg, Menne-Lothmann et al, 2019).…”
Section: Stress and Mental Healthmentioning
confidence: 99%